The lead tetra-acetate oxidations of some N-arylaminofumarates in the presence of trifluoroacetic acid - Sukari, Mohd Aspollah (Universiti Pertanian Malaysia, 1985)
p-Chloroanilino-, p-acetylanilino-, and p-toluidinojumarates are oxidized by lead tetraacetate in low yields to give oxanzlate. Similar oxidation of p-acetylan Nnofumarate in the presence of trifluoroacetic add affords only oxanilate. p- Toluidino and p-chloroanilinojumarates with lead tetra-acetateltrifluoroacetic acid give mixtures of oxazin, azobenzene and anzlide.